Opportunities of foreign language proficiency on the basis of computer training programs - Sarzhanova, G.B.; Romanenko, S.V.; Zatyneiko, А.М. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
This article is considered computer programmes in teaching foreign language in modern world, its usefulness and effectiveness. It considers effective ways of teaching at the English lesson. It shows a great interest of pupils in learning the language. Information and communication technology has affected language instruction in higher education. The advent of the Internet and the wide spread of technology in our life create new opportunities for language learning. The Internet is considered as the instrument in increasing their motivation, formation of strong language skills and improvement of foreign language skills.The article discusses the ways of forming information literate personality in the conditions of Digital Kazakhstan. It is also said that, based on advanced information technologies, computer-based training programs are capable of learning a foreign language and with the help of these programs improved skills in writing, listening,reading and speaking.
Компьютерлік оқыту бағдарламалары негізінде шетел тілін меңгеру мүмкіндіктері
Возможности овладения иностранным языком на основе компьютерных обучающих программ
Keywords: Internet; information technology; computer; exercise; education; foreign language training; educational materials